Microglia and Their Promising Role in Ischemic Brain Injuries: An Update - Yu, Luting; Su, Xiaojuan; Li, Shiping; Zhao, Fengyan; Mu, Dezhi; Qu, Yi (Frontiers in Cellular Neuroscience, 2020)
Ischemic brain injuries are common diseases with high morbidity, disability, and mortality rates, which have significant impacts on human health and life. Microglia are resident cells of the central nervous system. The inflammatory responses mediated by microglia play an important role in the occurrence and development of ischemic brain injuries. This article summarizes the activation, polarization, depletion, and repopulation of microglia after ischemic brain injuries, proposing new treatment strategies for such injuries through the modulation of microglia function.